THE ANALYSIS OF FIVE WILLIAM BLAKE'S POEMS - Sri Mulyati (LPPM Universitas Bina Sarana Informatika, 2019)
SARI Literature is art of written works used to describe written or spoken material or anything from creative writing to more technical or scientific works. Literature is beautiful works. Everyone can explore their imaginations, emotional, experiences, and ideas or whatever they feel or think by using poems, lyrics, fiction and nonfiction works, films or drama. The writer chooses poem as object of analysis. Because Poem is not only different than other types of literary works, but poem also has characteristic which makes poem different than ordinary speech or writing. The rhythm is unique, and there is beauty in it. Poem is one of art of written works in verse used to describe poet’s soul experiences, ideas or thoughts of the author.This analysis focus on poems by William Blake; ‘Ah sun flower’,’The Sick Rose’, ‘A Poison Tree’,’The Lamb’, and “London”. From five of those poems focus on the interinsic elements of poems,they are; diction,figure of speech. for advancing analysis writer uses a qualitative approach as a research metodology. While for analysing the three things, the writer uses a descriptive approach that reveals the themes of the five poems. The result of the analysis are; First,In analysing the dicition, the writer finds that the diction contains two meanings,they are connotation dan denotation meanings. Second, in analysing the figure of speech,the writer finds metaphor,personification,and hyperbola meanings. Then the third, in anaylising the theme the writer finds ; the theme of “Ah sun flower” is about death but is not the bad side of death, and the theme of